2006
DOI: 10.1073/pnas.0607668103
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis-independent tumor growth mediated by stem-like cancer cells

Abstract: In this work, highly infiltrative brain tumors with a stem-like phenotype were established by xenotransplantation of human brain tumors in immunodeficient nude rats. These tumors coopted the host vasculature and presented as an aggressive disease without signs of angiogenesis. The malignant cells expressed neural stem cell markers, showed a migratory behavior similar to normal human neural stem cells, and gave rise to tumors in vivo after regrafting. Serial passages in animals gradually transformed the tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
230
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 200 publications
(246 citation statements)
references
References 56 publications
3
230
1
6
Order By: Relevance
“…11,43 However, most glioma cell lines and primary glioma spheroids are easily propagated in serum-containing medium, and they are still tumorgenic in vivo when xenografted into animals. [24][25][26]44 In fact, a recent study reported that most of the cells in the C6 rat glioma cell line, exhibited cancer stem cell properties, regardless of whether they were CD133 positive or CD133 negative. 22 Thus, the ability of selfrenewal may not be exclusive to glioma cells expressing the CD133 marker but instead shared by many tumor phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11,43 However, most glioma cell lines and primary glioma spheroids are easily propagated in serum-containing medium, and they are still tumorgenic in vivo when xenografted into animals. [24][25][26]44 In fact, a recent study reported that most of the cells in the C6 rat glioma cell line, exhibited cancer stem cell properties, regardless of whether they were CD133 positive or CD133 negative. 22 Thus, the ability of selfrenewal may not be exclusive to glioma cells expressing the CD133 marker but instead shared by many tumor phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The 1st generation tumors did not exhibit contrast enhancement indicating intact vessel structures as previously described. 24,25 As in the patients, the addition of a contrast agent revealed a hyper-intense area in the high generation tumors indicating a compromised blood-brain-barrier (BBB) (Fig. 1b).…”
Section: Cd133 Expression Coincides With Onset Of Tumor Angiogenesismentioning
confidence: 99%
See 3 more Smart Citations